Perineal Massage During Pregnancy to Prevent Severe Perineum Laceration in Labor for Mrs. N - Nisriinaa Faadhilah; Diah Atmarina Y (Proceedings Series on Health & Medical Sciences, 2022)
As a woman, labor experience could be a best memory, but it was also became a trauma for them especially perineum laceration. Perineum laceration occurred during labor process naturally or instrumentally (episiotomy, extraction). Perineum laceration caused a discomfort and pain especially for heacting process. The trauma caused fearness and affected mother psychology. To minimize the perineum laceration, perineal massage could prevent the perineum laceration and perineum laceration grade II incidence. To determined the application of perineal massage, We did a case study report using descriptive method for Mrs. N 28th years old, second gravide, in Sudagaran Village, Banyumas Regency. Perineal massage was applied for 3 times during the pregnancy visit starting at 29 weeks of gestation and also 2-3 times a week by herself. The labor outcome showed there was nothing perineum laceration occurred during labor. Therefore, perineal massage should be routinely apply to minimize severe perineum laceration incidence.